2019
DOI: 10.3390/cells8070735
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Green Alga Chlamydomonas reinhardtii to the DNA Damaging Agent Zeocin

Abstract: DNA damage is a ubiquitous threat endangering DNA integrity in all living organisms. Responses to DNA damage include, among others, induction of DNA repair and blocking of cell cycle progression in order to prevent transmission of damaged DNA to daughter cells. Here, we tested the effect of the antibiotic zeocin, inducing double stranded DNA breaks, on the cell cycle of synchronized cultures of the green alga Chlamydomonas reinhardtii. After zeocin application, DNA replication partially occurred but nuclear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…We first confirmed that inactivation of KU80 , KU70 , and POLQ caused the expected sensitivity to the drug Zc which creates DSBs ( Ehrenfeld et al 1987 ; Chankova et al 2007 ; Chen et al 2008 ; Čížková et al 2019 ). Surprisingly, polQ cells were found to be more sensitive to Zc than ku80 and ku70 cells.…”
Section: Resultssupporting
confidence: 55%
“…We first confirmed that inactivation of KU80 , KU70 , and POLQ caused the expected sensitivity to the drug Zc which creates DSBs ( Ehrenfeld et al 1987 ; Chankova et al 2007 ; Chen et al 2008 ; Čížková et al 2019 ). Surprisingly, polQ cells were found to be more sensitive to Zc than ku80 and ku70 cells.…”
Section: Resultssupporting
confidence: 55%
“…There were also some phenotypic markers that overlapped with certain chemicals. For example, cells treated with H 2 O 2 and zeocin, a DNA damaging agent, 28 both garnered the same top three chloroplast normalized moment features. However, the VIP ranking order of these phenotypic markers and the overall combination of markers were still distinct between chemical profiles.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…There is a scarcity of data [ 40 ] indicating that H 2 O 2 and NO can modify algal cell development by influencing the expression of cell cycle-related proteins, such as cyclin and cyclin-dependent kinases and histone proteins [ 5 , 41 ]. These examples form a basis for establishing the role of ROS and RNS in the cell cycle of green algae, both as the signals directly involved in the regulation of protein expression required for completing the cell cycle, and as factors involved in the regulation of photoautotrophic growth [ 42 ], which, in turn, allow the cell to attain the commitment competence.…”
Section: H 2 O 2 and No Cross-talkmentioning
confidence: 99%